Pengaruh Penggunaan Bahan Bakar Biodisel Berbasis Biji Buah Nyamplung (Calophyllum Inophyllum) Terhadap Emisi Gas Buang Mesin Diesel. - Persulesy, Pieter Y; K, Basri; Suprapto, Edy (Universitas Nusa Cendana, 2022)
One of the energy sources used as a substitute for diesel is biodiesel, which is an energy source made from plants and animals. One of the plant species that can be developed for biodiesel in Indonesia is the Nyamplung tree (Calophyllum inophyllum). The purpose of this study was to determine the effect of using biodiesel fuel based on nyamplung fruit seed oil (Calophyllum Inophyllum) on exhaust gas emissions of CO, CO2, NOx, O2, and diesel engine opacity. The study used a non-factorial Randomized Block Design (RAK) basic pattern which was repeated 3 times, including: X1 : Pure Diesel (100%), X2 : Mixture of Diesel and 50% Biodiesel (B50), X3 : 100% Biodiesel (B100), Y : Exhaust Emissions (CO, CO2, NOx, O2 and Opacity). From the analysis of variance, it was found that the use of nyamplung seed biodiesel fuel on exhaust gas emissions of CO, CO2, NOx, O2, and Opacity had a significant effect on the 1% and 5% levels in the treatment and had no significant effect on the test group. Then it can be said that the use of biodiesel can reduce exhaust emissions.